PENGUATAN MODERASI BERNEGARA BERBASIS PROBLEM BASED LEARNING (PBL) DALAM PEMBELAJARAN MATAKULIAH PENDIDIKAN AGAMA ISLAM (MK PAI) - Yulianti, Yulianti; Sultoni, Achmad (TARBAWY: Indonesian Journal of Islamic Education, 2024)
The aim of this research is to formulate a plan to strengthen religious moderation using the PBL model in learning PAI courses. To achieve this goal, the library research method was used, namely reviewing books and articles related to religious moderation, MK PAI and PBL, which ended by linking these three things to obtain a formula for implementing PBL in MK PAI to strengthen religious moderation. The research produced a number of steps to enhance religious moderation using the PBL model. First, determine the relevant subject matter; second, assess learning outcomes; third, determine teaching materials and learning media; fourth, formulate steps for implementing PBL with 5 stages; orientation of students to problems, organizing students, guiding investigations, developing presentation of results, analyzing and evaluating problems; Thus, it can be concluded that there are four steps to use technology in PAI lectures to strengthen religious moderation through the PBL model.